(untitled) (Journal of Educational Sciences, 2025)
This article examines periphrasis as a distinct stylistic device in linguistics. It provides a comprehensive analysis of both international and Kazakh scholarly research on periphrastic expressions. The study evaluates linguists’ conclusions from a contemporary perspective and identifies the defining features of periphrasis. Researchers who have investigated the lexical structure of the Kazakh language link periphrasis with various expressive means. Most scholars argue that periphrasis requires further scientific analysis, particularly in relation to metaphor, metonymy, synecdoche, euphemism, taboo, word combinations, compound words, and phraseological units, based on shared and distinctive semantic and structural characteristics. In modern communication, periphrasis plays a significant role in conveying meaning concisely while enhancing the aesthetic quality of the language. The article compares key scholarly definitions and interpretations of periphrasis, demonstrating that its boundaries with other linguistic units remain insufficiently defined. Examples from Abai’s works illustrate the function of periphrasis in expressing ideas figuratively. To determine future philology specialists’ understanding of the concept of periphrase, a survey was conducted, and its results are described and concluded. 66 students from Abai Kazakh National University participated in the survey, studying the "6B01701 - Kazakh Language and Literature" program. Keywords: periphrasis, the phenomenon of periphrasis, figurative meaning, stylistic device, epithet, study.